2021
DOI: 10.1186/s13018-021-02316-6
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of dual-mobility total hip arthroplasty versus bipolar hemiarthroplasty for patients with femoral neck fractures: a systematic review and meta-analysis

Abstract: Background Elderly patients with femoral neck fractures are at a higher risk of dislocation after hip arthroplasty procedures. In comparison with total hip arthroplasty (THA), bipolar hemiarthroplasty (HA) and dual-mobility total hip arthroplasty (DM-THA) can be an effective alternative treatment which increases the effective head size and overall stability of the prosthesis. We aim to review the current evidence on the outcome after DM-THA and HA for femoral neck fractures in the elderly. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 28 publications
0
10
0
1
Order By: Relevance
“…HHA is the preferred treatment option for displaced FNF, as it is faster and leads to satisfactory function and performance in the elderly [20][21][22][23]. In HHA, surgeons can choose to use a unipolar or bipolar femoral head, using the latter to maximize the longevity of the implant.…”
Section: Introductionmentioning
confidence: 99%
“…HHA is the preferred treatment option for displaced FNF, as it is faster and leads to satisfactory function and performance in the elderly [20][21][22][23]. In HHA, surgeons can choose to use a unipolar or bipolar femoral head, using the latter to maximize the longevity of the implant.…”
Section: Introductionmentioning
confidence: 99%
“…Many meta-analyses consider THA to be superior to HA in patients with femoral neck fractures [ 11 13 ]. On the other hand, many other meta-analyses find no relevant overall difference in outcome between HA and THA in patients with femoral neck fractures [ 10 , 14 , 65 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…Male patients are more likely to have an acetabular component size that accommodates a large femoral head, and this may explain the slightly higher percentage of THAs performed in men, given our inclusion criteria. Systematic reviews have concluded that DM bearings are equivalent, or superior, to large femoral bearings in reducing the risk of dislocation in primary and revision surgery [61][62][63][64] and have a lower risk of dislocation and revision than HA 65 . Systematic reviews have supported the use of DM bearings as a viable option for FNF 66 .…”
Section: Discussionmentioning
confidence: 99%